Cytotoxic labdane diterpenes and bisflavonoid atropisomers from leaves of Araucaria bidwillii. Issue 21 (25th May 2017) - Ebada, Sherif S.; Talaat, Aya N.; Labib, Rola M.; Mándi, Attila; Kurtán, Tibor; Müller, Werner E.G.; Singab, AbdelNasser; Proksch, Peter
Abstract: Chemical investigation of a methanolic extract of leaves from Araucaria bidwillii (Araucariaceae) from Egypt afforded four new labdane diterpenoidal metabolites (1 –4 ) together with one known diterpene, 7-oxocallitrisic acid (5 ), two triterpenoidal metabolites, 2- O -acetyl-11-keto-boswellic acid (6 ) and β -sitosterol-3- O -glucopyranoside (7 ), phloretic acid (8 ), and two methylated bisflavonoids, agathisflavone-4′, 7, 7″-trimethyl ether (9 ) and cupressuflavone-4′, 7, 7″-trimethyl ether (10 ). The new metabolites1 –4 were unambiguously identified by applying extensive 1D and 2D NMR spectroscopic studies as well as HRESIMS. The relative and absolute configurations of1 –4 were determined using ROESY and the modified Mosher's method, respectively. All isolated compounds were assessed for their antimicrobial, antitubercular and cytotoxic activities. Among the tested compounds, the new labdane diterpenes1 –4 revealed significant cytotoxic activity against mouse lymphoma L5178Y cell line with IC50 values ranging from 1.4 to 12.9 μM, respectively. Graphical abstract: